Anti‐CD20 therapy for multiple sclerosis‐associated uveitis: A case series. (13th July 2022) - Stascheit, Frauke; Rübsam, Anne; Otto, Carolin; Meisel, Andreas; Ruprecht, Klemens; Pleyer, Uwe
Abstract: Background and purpose: Approximately 1% of patients with multiple sclerosis (MS) have uveitis, but data on the effects of immunotherapies for MS on MS‐associated uveitis are scarce. The aim of this study was to investigate the ophthalmological outcomes in patients with MS‐associated uveitis treated with anti‐CD20 therapy. Methods: A retrospective study of 12 eyes of six patients with MS‐associated uveitis, refractory to previous immunotherapies, was conducted. Uveitis activity was assessed before initiation of anti‐CD20 therapy and at regular follow‐up visits. Primary outcome measures were: vitreous haze score; retinal vasculitis score, determined on fluorescein angiography images; macular edema, as quantified by central retinal thickness (CRT) on optical coherence tomography; and visual acuity (VA). Secondary outcomes included number of annualized uveitis or MS relapses, disease activity on cerebral magnetic resonance imaging (cMRI) and Expanded Disability Status Scale (EDSS) score. Results: After a median (interquartile range [IQR]) treatment time of 28.5 (8–43) months, anti‐CD20 therapy was associated with an improvement of vitreous haze score ( p = 0.002), retinal vasculitis score ( p = 0.001), CRT ( p = 0.002), and VA ( p = 0.007). The median (IQR) annualized uveitis relapse rate declined from 0.59 (0.56–0.94) before to 0 (0–0.49) after the start of anti‐CD20 therapy. The median (IQR) annualized MS relapse rate declined from 0.62 (0.26–2.84) before to 0 (0–0) after the start of anti‐CD20 therapy. After initiation of anti‐CD20 therapy, there was no disease activity on cMRI, and EDSS score improved ( n = 2) or remained stable ( n = 4). No severe adverse events were observed. Conclusion: These findings suggest that anti‐CD20 therapy may be a valuable treatment option for MS‐associated uveitis. Abstract : Approximately 1% of patients with multiple sclerosis (MS) have uveitis, but data on the effects of immunotherapies for MS on MS‐associated uveitis are scarce. In a retrospective study of 12 eyes of six patients with MS‐associated uveitis refractory to previous immunotherapies, we investigated the ophthalmological and neurological outcomes in patients with MS‐associated uveitis treated with anti‐CD20 therapy. Our findings suggest that anti‐CD20 therapy may be a valuable treatment option for MS‐associated uveitis.